The European Project Semester at ISEP: the challenge of educating global engineers - Malheiro, Benedita (2014)
Current engineering education challenges require approaches that promote scientific, technical, design and complementary skills while fostering autonomy, innovation and responsibility. The European Project Semester (EPS) at Instituto Superior de Engenharia do Porto (ISEP) (EPS@ISEP) is a one semester project-based learning programme (30 European Credit Transfer Units (ECTU)) for engineering students from diverse scientific backgrounds and nationalities that intends to address these goals. The students, organised in multidisciplinary and multicultural teams, are challenged to solve real multidisciplinary problems during one semester. The EPS package, although on project development (20 ECTU), includes a series of complementary seminars aimed at fostering soft, project-related and engineering transversal skills (10 ECTU). Hence, the students enrolled in this programme improve their transversal skills and learn, together and with the team of supervisors, subjects distinct from their core training. This paper presents the structure, implementation and results of the EPS@ISEP that was created in 2011 to apply the best engineering practices and promote internationalisation and engineering education innovation at ISEP.